2019
DOI: 10.15252/emmm.201810058
|View full text |Cite|
|
Sign up to set email alerts
|

Anti‐tumor effects of PIM / PI 3K/ mTOR triple kinase inhibitor IBL ‐302 in neuroblastoma

Abstract: The PI 3K pathway is a major driver of cancer progression. However, clinical resistance to PI 3K inhibition is common. IBL ‐302 is a novel highly specific triple PIM , PI 3K, and mTOR inhibitor. Screening IBL ‐302 in over 700 cell lines representing 47 tumor types identified neuroblastoma as a strong candidate for PIM / … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 42 publications
1
13
0
Order By: Relevance
“…AUM302 and the combination of AZD-1208 + BEZ235 affect a different set of genes and phosphoproteins, despite theoretically targeting the same proteins. AUM302 seems to affect similar genes to AZD-1208, which might suggest it preferentially targets the PIM pathway, despite exhibiting a lower IC50 for PIK3CA 20 . The combination of AZD-1208 + BEZ235, appears to exhibit greater inhibitory effects towards PI3K/mTOR.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…AUM302 and the combination of AZD-1208 + BEZ235 affect a different set of genes and phosphoproteins, despite theoretically targeting the same proteins. AUM302 seems to affect similar genes to AZD-1208, which might suggest it preferentially targets the PIM pathway, despite exhibiting a lower IC50 for PIK3CA 20 . The combination of AZD-1208 + BEZ235, appears to exhibit greater inhibitory effects towards PI3K/mTOR.…”
Section: Discussionmentioning
confidence: 97%
“…With an IC50 an order of magnitude lower than the AZD-1208 + BEZ235 combination, the multikinase inhibitor could potentially reduce adverse effects and allow for the co-targeting approach to be used clinically. Mohlin et al also reported the IC50 for AUM302 in neuroblastoma models to be in the nanomolar range 20 . Furthermore, adverse effects are a major issue of nontargeted prostate cancer treatments 37 ; the development of new therapeutic strategies that would have less impact on the patients' quality of life could significantly improve the current standard of care.…”
Section: Discussionmentioning
confidence: 98%
“…In preclinical studies IBL-202, a dual targeting PIM and PI3K inhibitor, has demonstrated superior cytotoxic activity in CLL cells in vitro compared to PI3K inhibitor Idelalisib alone, in addition to significantly reducing the proliferative, migratory capacity of leukaemia cells (Crassini, 2018). cisplatin inhibited neuroblastoma PDX growth (Mohlin et al, 2019). IBL-302 may also benefit one third of patients with breast cancer who have a mutated PI3K pathway and those with resistant triple negative breast cancer who have high PIM kinase expression (Horiuchi et al, 2016).…”
Section: Targeting Pim Kinase Via Dual-targeted Inhibitorsmentioning
confidence: 99%
“…We have previously shown that the PI3K pathway regulates HIF-2α specifically via mTORC2 and in addition is a promising treatment strategy using a triple PIM/PI3K/mTOR inhibitor in trunk neural crest-derived tumor form neuroblastoma. 27,28 Thus, this would be an interesting mechanism to investigate further. Given the effects we observed on embryonic development in vivo, we mapped potential upstream regulators of arrest in embryo growth (one of the identified top processes by RNA sequencing data).…”
Section: Rna Sequencing After Loss Of Hif-2α Identifies Downstream mentioning
confidence: 99%
“…Of note, we have recently identified that PI3K-mTORC2 regulates HIF-2α expression and functions as a valid treatment target in neuroblastoma. 27,28 Genes associated with migration of tumor cells mainly encode for plasma membrane and secreted proteins, including several members of the matrix metalloproteinase (MMP) family. MMPs promote invasion and migration by degrading components of the extracellular matrix and have been shown to be regulated by HIF-2α in several different tumor forms, 37,38 further reinforcing a possible connection between HIF-2α, trunk neural crest cells and invasive migratory behavior.…”
Section: Cdx2 and Hnf1b Are Predicted Mediators Of Observed In Vivomentioning
confidence: 99%